PENGARUH UKURAN PERUSAHAAN, LEVERAGE, INTENSITAS PERSEDIAAN DAN INTENSITAS ASET TETAP TERHADAP PENGHINDARAN PAJAK (Studi Kasus pada Perusahan Manufaktur yang Terdaftar di BEI Tahun 2015-2017) - Simamora Angelina Chintia; Fitrios Ruhul; Fajar Odiatma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to analyze the effect of firm size, leverage, inventoryintensity and intensity of fixed assets on tax avoidance in manufacturingcompanies listed on the Indonesia Stock Exchange in 2015-2017. This researchuses secondary data, namely annual reports that can be accessed from theIndonesia Stock Exchange website www.idx.co.id. The population in this studywere 152 manufacturing companies. The sampling method used in this study waspurposive sampling. Based on this method a sample of 54 companies wasobtained, with a research period of 3 years. Thus, the amount of data usedamounts to 162 observation data. Analysis of the data used in this study ismultiple regression analysis and test coefficient of determination (R2 test). Beforethe analysis of the data is carried out, first a classic assumption is tested to testthe feasibility of the data.The results of this study indicate that the variable size ofthe company does not have a significant effect on tax avoidance. Meanwhile, theleverage variable and the intensity of fixed assets have a significant negativeeffect on tax avoidance. And inventory intensity variables have a significantpositive effect on tax avoidance.Keywords : tax avoidance, company size, leverage, inventory intensity, and fixedasset intensity